2016
DOI: 10.1007/s40003-016-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of AquaCrop Model to Different Irrigation Schedules for Irrigated Cabbage

Abstract: Agricultural sector faces the challenge to produce more food with less water by increasing crop water productivity. As such, the question of improving the present level of crop water productivity in general and for irrigation in particular assumes a great significance in perspective water resource planning. This study was undertaken to improve water productivity, i.e., 'more crop per drop.' In this study response of cabbage to different irrigation schedules under mulch and non-mulch condition using calibrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…The performance of the model was found to be good as described by the of 0.91. The results also concur with those of Pawar, Kale [23] who carried out a research in India where the model was able to simulate biomass with a NSE of 0.96. A study by Lievens [24] carried out in North Eastern Thailand revealed that Aquacrop model was able to relate well the simulated to the actual biomass of sweet corn with a root mean square error (RMSE) of 0.56.…”
Section: Simulation Of Tomato Water Productivity Using Aquacrop Modelsupporting
confidence: 89%
“…The performance of the model was found to be good as described by the of 0.91. The results also concur with those of Pawar, Kale [23] who carried out a research in India where the model was able to simulate biomass with a NSE of 0.96. A study by Lievens [24] carried out in North Eastern Thailand revealed that Aquacrop model was able to relate well the simulated to the actual biomass of sweet corn with a root mean square error (RMSE) of 0.56.…”
Section: Simulation Of Tomato Water Productivity Using Aquacrop Modelsupporting
confidence: 89%
“…The contrast between Bello and Walker (2017) with our results might be that; (1) they did not account for the fact that amaranth was harvested repeatedly during the growing period, (2) the effective rooting depth was not measured but estimated from literature, and (3) they used an empirical equation to convert leaf area index (LAI) to CC, which might have underestimated CC. Studies by Greaves and Wang (2017), Pawar et al (2017), and Razzaghi et al (2017) showed that AquaCrop was capable of simulating CC for maize, cabbage and potato, but not under water-stressed conditions. The strength of AquaCrop is its ability to separate ETa into soil evaporation (Es) and transpiration (Tr) Raes et al, 2009;Steduto et al, 2009), which enables the assessment of productive (Tr) and non-productive (Es) water use.…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenge to compare WP from different locations because of varying climatic conditions, methods used in calculating WP, irrigation water management, soil fertility management, and vapour pressure deficit (Zwart and Bastiaanssen, 2004); other studies report the total amount of water applied, whereas others report ETa. For example, Pawar et al (2017) reported WPETa of cabbage ranging from 50 to 69 kg ha -1 mm -1 , however, the denominator was total irrigation water applied. Wenhold et al (2012) benchmarked WPETa of leafy vegetables using a dataset (AGB per ETa) that was derived from different literature sources and reported values ranging from 2 to 90 kg ha -1 mm -1 for selected leafy vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling can be conducted from 120 cm soil depth [3]. Usually soil profile study was allowed to demonstrate the soil characteristics at experimental field and determined the analysis of physicochemical belongings [5]. In this model, the condition of soil water in the lower, middle and upper positions has been measured as the input of the AquaCrop model in order to predict the water use efficiency of the sugarcane [6].…”
Section:  Soil Profile Datamentioning
confidence: 99%